Level and distribution of secreted and cell-associated N-acetyl, N-glycolylneuraminic, and deaminoneuraminic acids in osteosarcoma cells isolated from patients - Thanyaluck Phitak (2018)
© 2017, Science Society of Thailand under Royal Patronage. All rights reserved. Sialic acids, which are members of a family of 9-carbon carboxylated sugars, usually occupy the terminal position of the glycan chains of glycoconjugates and play an important role in various biological processes. N-acetylneuraminic acid (Neu5Ac) and N-glycolylneuraminic acid (Neu5Gc) are the dominant sialic acids in mammals, whereas deaminoneuraminic acids (KDN) can be detected in trace amounts. The increase of sialic acid levels has been reported in relation to the pathology and aggressiveness of cancer. Here we used a fluorometric-HPLC method to investigate the level and distribution of Neu5Ac, Neu5Gc, and KDN in osteosarcoma cells isolated from 7 patients and compare them with those in osteoblasts isolated from 3 patients with other bone diseases. Both cell types expressed all three sialic acids with abundances Neu5Ac > Neu5Gc > KDN. Total sialic acid levels in osteosarcoma cells were twice that in osteoblast cells. Only cell-associated Neu5Ac and Neu5Gc levels were higher, but not secreted forms. However, cell-associated and secreted KDN levels were not significantly different among those two groups. This suggests that the level and distribution of sialic acids in osteosarcoma cells were different from those in normal osteoblast cells. Thus their level, type, and distribution may be related to the pathology of osteosarcoma.